The Peculiarities of the Folk Botanical Terminology in the Ukrainian Western-Polissian Dialects (Linguostylistic Studies, 2018)
The article deals with the investigation of the lexical structure of Western-Polissian dialect which presents a particular interest as far as it concerns lexics reflecting different language changes in local dialect since the Western-Polissian dialect preserves the real treasure for slavic philology. The lexical and theme groups are analyzed in this work. The botanical vocabulary group appeared to be the oldest and the most valuable one for learning in the course of the study of the history of language. The analysis has been carried out from the semantic-motivation point of view. It has been revealed that one part of the names have direct motivation and the other – indirect motivation. Few names can be motivated in different ways. The names of the plants in the Western-Pollisian dialect form a theme group of vocabulary that is rich in the repertoire, high level of representation and the nominative variability of designations. Changing the meaning from well-known trees and shrubs to those phyto-objects that are known only to individual dialect native speakers, they also depend on the expanded range of the plants in the studied area, on the place of their growth, life form, nutritional and medicinal properties. Most plant names are monolexemes. Analytical names are represented mainly by the type of attribute phrase. The repertoire of the names indicates the formal variation of the Western-Pollisian dialect at the phonemic, accent and grammatical levels. The article deals with the topical group of the names of plants which are quite ancient and worth studying in the course of the history of language. In the focus of consideration are the semantic transformations in the result of metonymical changes based on botanical vocabulary, the so-called metonymic transference. It has been revealed that semantic derivatives are the result of the associative connections caused by spatial, time-based or logical contiguity. The author differentiates metonymy proper and the metonymy complicated by derivation. The characteristic peculiarity of the analyzed group of words is presence of absolute synonyms for many notions. Often, in one settlement or even in the respondent’s conversation several notions are used to denote the same phenomenon. Majority of the literary names, especially of foreign origin, have several phonetic, morphologic оr accentuation variants.
Keywords: botanical lexics; lexeme; phytological nominations; Western Polissian dialects; semantic models; nominative variability; lexical variability